Freedom of contract: the evolution of a legal principle in the era of information - V. A. Boldyrev; V. A. Maksimov (Правоприменение, 2025)
The subject of the article is new patterns observed in approaches to the principle of freedom of contract from legal science and law enforcement practice.The purpose of the article is to show the directions of evolution of the principle of freedom of contract in connection with the influence of information technology on civil circulation and changes in the significance of this principle for law enforcement.Main results, scope of application. In science, there is a transformation of ideas about the principle of freedom of civil contract. To the provisions of the codified civil law, reflecting the basic postulates of the principle of freedom of contract, modern researchers add freedom to choose the form, as well as the method (order) of its conclusion. This principle turns out to be actually limited by a technological innovation – a smart contract, for which the possibility of changing and terminating the contract, as a rule, is absent. The expansion of freedom of contract is observed in the circulation of new objects of civil rights  – cryptocurrencies. Research in the field of neurophysiology (neuromarketing) calls into question human free will, and with it the freedom of contract. The collected statistical data characterizing the content of judicial acts allows us to state a pattern in recent years – a lesser orientation of courts considering economic disputes towards the principle of freedom of contract. The increasing role of centralized legal regulation of civil relations leads to a decrease in the role of autonomous regulation, and therefore a decrease in the importance of the principle of freedom of contract. The observed trend of growth in the number of norms in legislative acts can hardly be called positive – its continuation can lead to a deterioration in the skills of participants in civil transactions to develop flexible economic decisions, a decrease in responsibility and the level of legal culture. The results obtained will be useful for improving lawmaking.The research methodology is represented by statistical, formal logical, formal dogmatic and comparative research methods.Conclusions. Cycles of growth and decline in the importance of the principle of freedom of contract for law enforcement practice are in organic connection with the number of legal norms regulating civil relations, institutional transformations and changes in the approach to the official interpretation of the law. Lawmakers should ensure greater stability of legislation regulating this area of civil relations.